Alterations of regional cerebral blood flow after NMDA receptor antagonist administration in patients with alcohol‐related dementia. Issue 4 (20th November 2017) - Chon, Younghoon; Jeong, Hyeonseok S.; Im, Jooyeon J.; Oh, Jin Kyoung; Kim, Young‐Do; Chung, Yong‐An; Kim, Dai‐Jin
Abstract: Although N ‐methyl‐d ‐aspartate (NMDA) receptor antagonists may have beneficial influences on cognition in patients with alcohol‐related dementia (ARD), their effects on regional cerebral blood flow (rCBF) remain unknown. This study evaluated changes in rCBF in ARD patients after administration of NMDA receptor antagonist for 12 weeks using technetium‐99m ethyl cysteinate dimer (Tc‐99m ECD) single‐photon emission computed tomography (SPECT). Twenty‐eight ARD patients were administered memantine for 12 weeks and underwent clinical evaluations and brain SPECT scans at baseline and follow‐up. Whole‐brain changes in perfusion were examined on a voxel‐by‐voxel basis. At follow‐up, the patients showed reduced rCBF in the left medial frontal gyrus, left cingulate gyrus, left claustrum, right brainstem, left superior temporal gyrus, bilateral fusiform gyrus, and left cerebellum. On the other hand, increased rCBF was found in the bilateral uncus, left parahippocampal gyrus, bilateral superior frontal gyrus, right inferior parietal lobule, left cuneus, and left superior temporal gyrus. Perfusion increases in various brain areas including the superior frontal, parahippocampal, and inferior parietal areas, which may play important roles in the pathophysiology of ARD, suggest potential benefits of NMDA receptor antagonists on brain functions in patients with ARD.